2014
DOI: 10.2478/bhk-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

The new system of the talent development program in Hungarian soccer

Abstract: Summary Study aim: due to a series of failures and the drastic reduction in the quality of Hungarian soccer, greater emphasis should be put on coaches’ professional development and talent development programs. The aim of this study was to present the newly established Hungarian Soccer Development Program that focuses on the development of youth talent. Methods: document analysis and in-depth interviews were utilized during the research process. All Program leaders were interviewed in the Hungarian Soccer D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nonetheless, other parameters (e.g. skills, motivation, technique and cognitive functions) [12,32] should not be omitted. For instance, the football players in the first Polish league were found to be faster in the 20 m (3.04 s) sprint than their counterparts in the fourth league (3.11 s) [40], while the elite players had a better performance in the 10 m (1.93 s) sprint than the average (2.00 s) and the below-average football players (2.04 s) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other parameters (e.g. skills, motivation, technique and cognitive functions) [12,32] should not be omitted. For instance, the football players in the first Polish league were found to be faster in the 20 m (3.04 s) sprint than their counterparts in the fourth league (3.11 s) [40], while the elite players had a better performance in the 10 m (1.93 s) sprint than the average (2.00 s) and the below-average football players (2.04 s) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The creation of an operating system and club model that allows for the utilization of resourcesmaximized market revenues and governmental sources -in the most effective way is an unavoidable challenge (Csáki et al, 2014;Vincze et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades, it has been proven that the identification and selection of talented players lasts several years, is based on many different factors, and, furthermore, is also influenced by many factors in the talent development process (Lawrence, 2008;Csáki et al, 2014). Our results support the earlier studies (Christensen, 2009; that found the monitoring of players to be important throughout the whole process of talent development through different tests and measurements and, also of great significance, through the eyes of the coach.…”
Section: Discussionmentioning
confidence: 99%